A note on identifying heterogeneous sharing rules - Pierre-André Chiappori; Ju Hyun Kim (Quantitative Economics, 2017)
In this note, we address nonparametric identification of a collective model of household behavior in the presence of additive unobserved heterogeneity in the sharing rule. We show that the (nonstochastic part of the) sharing rule is nonparametrically identified. Moreover, under independence assumptions, individual Engel curves and the random distributions are identified except in special cases (i.e., linear Engel curves).
Keywords: C14; C31; D10; D11; D13; 330; Sharing rule; unobserved heterogeneity; collective models; nonparametric identification